2010
DOI: 10.1093/mutage/geq070
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei and pesticide exposure

Abstract: Micronucleus (MN) is a biomarker widely used in biomonitoring studies carried out to determine the genetic risk associated to pesticide exposure. Many in vitro and in vivo studies, as well as epidemiological approaches, have demonstrated the ability of certain chemical pesticides to produce genetic effects including cancer and other chronic pathologies in humans; thus, biomonitoring studies have been carried out to characterise the genetic risk associated to pesticide exposure. It must be noted that 'pesticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 54 publications
0
83
0
18
Order By: Relevance
“…According to Buckley et al (2000) and Meinert et al (2000), increased incidences of leukemia and non-Hodgkin lymphomas can be observed for individuals exposed to pesticides. A meta-analysis showed that farmers were at risk of specifi c tumors including leukemia and multiple myeloma (Bolognesi 2003, Bolognesi et al 2011. Bull et al (2006) and Bolognesi et al (2011) argued that the assessment of cytogenetic effects in exposed subjects might act as an early indicator for an increased risk to develop cancer, although the evidence presented was somewhat contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Buckley et al (2000) and Meinert et al (2000), increased incidences of leukemia and non-Hodgkin lymphomas can be observed for individuals exposed to pesticides. A meta-analysis showed that farmers were at risk of specifi c tumors including leukemia and multiple myeloma (Bolognesi 2003, Bolognesi et al 2011. Bull et al (2006) and Bolognesi et al (2011) argued that the assessment of cytogenetic effects in exposed subjects might act as an early indicator for an increased risk to develop cancer, although the evidence presented was somewhat contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes responsible for interindividual differences in the ability to activate or detoxify genotoxic substances are recognized as biomarkers of susceptibility towards mutations, cancer, and other diseases (Zeljesic and Garaj-Vrhovac 2001, Bolognesi 2003, Bolognesi et al 2011. Paraoxonases (PON) are responsible for the metabolism of organophosphate-based insecticides (Bolognesi 2003), and many enzymatic isoforms, such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…El uso del ensayo de MN en mucosa bucal es utilizado como blanco para determinar la inducción de daño genotóxico por exposición a plaguicidas. En América Latina se han ejecutado cuatro trabajos que utilizaron este ensayo, realizados en Bolivia (Larrea Poma et al 2010), Brasil y Costa Rica (Castro et al 2004, Bortoli et al 2009, Pértile Remor et al 2009), en una revisión en la cual se presentan 13 estudios poblacionales en mucosa bucal (Bolognesi et al 2011). En las pruebas utilizadas, EC y MN, los citados autores encontraron un incremento significativo (p < 0.05) de daño genotóxico en los agricultores expuestos a plaguicidas, en relación a los GR (Larrea Poma et al 2010), semejantes a los resultados obtenidos por Bortoli et al (2009), quienes también utilizaron la prueba de MN.…”
Section: Cuadro II Características De Las Prácticas Agrícolas En El unclassified
“…Los biomarcadores de daño genético más utilizados en poblaciones expuestas a plaguicidas son AC, ICH y MN a partir de muestras de sangre periférica y MN en epitelio bucal, así como, EC en sangre periférica , Gómez-Arroyo et al 2013). El ensayo de MN en células exfoliadas del epitelio bucal no requiere del cultivo de células, por lo tanto además de ser un método mínimamente invasivo y con una obtención de la muestra en forma sencilla, requiere un menor tiempo de realización comparado con los estudios en sangre (Pastor et al 2003, Martínez-Valenzuela et al 2009, Bolognesi et al 2011, Benedetti et al 2013. Este método permite detectar daño al ADN, inestabilidad cromosómica, muerte celular, el potencial regenerativo del tejido de la mucosa bucal ), anomalías asociadas con defectos genéticos en el mantenimiento del genoma, envejecimiento acelerado y algunas enfermedades degenerativas.…”
Section: Introductionunclassified
“…Recently, many biomonitoring studies have investigated biomarkers of cytogenetic damage including chromosomal aberrations (CA), sister chromatids exchange (SCE) and cytokinesisblock micronucleus (CBMN) among pesticide-exposed population. Among them, CBMN in human peripheral blood lymphocytes is one of the most extensively studied biomarkers of cytogenetic damage (Bolognesi et al, 2011). However, a single study with relatively small sample may not be sufficient to present a robust evidence of the relationship between pesticides exposure and increased frequencies of CBMN in human peripheral blood lymphocytes.…”
Section: Introductionmentioning
confidence: 99%